An integrated approach to evaluating sustainability in supply chains using evolutionary game theory. (January 2018) - Babu, Sujatha; Mohan, Usha
Highlights: Addresses gap indicated by Brandenberg et al.in holistic supply chain sustainability. Studied across multiple dimensions-environment, social, economic, cultural & governance. We use Evolutionary Game Theory to model stakeholders & payoff functions. Sustainability identified with equilibrium of system over finite period of time. Allows us to study factors that can cause shift in equilibrium over time. Abstract: Sustainability in supply chains is typically studied across one or more dimensions such as environmental, social, economic, culture and governance. Traditionally sustainability in supply chains has focused on environmental dimensions, while a few have attempted to focus on social and economic dimensions without really integrating them. There has been only a small effort to define sustainability by integrating all relevant dimensions (a holistic approach). This paper proposes to fill this gap. We identify sustainability of a supply chain with the equilibrium of the system over a long (but finite) period of time after integrating the various dimensions. Thus it necessitates looking at factors that can cause a shift in the equilibrium. Towards this, we propose to build a strong theoretical framework to integrate, explain, and predict sustainability for supply chains using cross-disciplinary effort. In our theoretical framework, evolutionary game theory serves as the pure conceptual theory-building tool, the metrics are qualitative in nature and the indicators are quantitative statistical measures. The use of evolutionary game theory concepts allows us to understand how sometimes trivial actions by members of the supply chain can trigger cascading effects that can move the system away from equilibrium. One of the salient aspects of our model is its complete scalability in terms of changes to the dimensions and metrics. As an example, we explain and predict social and economic sustainability (in tandem) for a public health insurance supply chain using evolutionary game theory.